2009
DOI: 10.1007/s10600-009-9446-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and cytotoxic activities of polyketides produced by the mangrove endophytic fungus Phomopsis SP. ZSU-H76

Abstract: A new polyketide, 2-(7′-hydroxyoxooctyl)-3-hydroxy-5-methoxybenzeneacetic acid ethyl ester (1), together with three known compounds dothiorelone A (2), B (3), and C (4) were isolated from the mangrove endophytic fungus Phomopsis sp. ZSU-H76 obtained from the South China Sea. Their structures were elucidated by spectroscopic methods, mainly 1D and 2D NMR spectroscopic techniques. Primary bioassays showed that 1 exhibited cytotoxicity against HEp-2 and HepG2 cells with IC 50 values of 25 and 30 μg/mL, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Our results and previous reports (Brady et al 2000;Huang et al 2008Huang et al , 2009 showed that cytosporones, and possibly the related dothiorelones (Fig 2), are produced by members of Phomopsis, Cytospora, and Cytospora-like, although the distribution of these metabolites among different species in each genus is not known. No strain of chemotypes 2e5 was found to produce cytosporones or dothiorelones (Table 2).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results and previous reports (Brady et al 2000;Huang et al 2008Huang et al , 2009 showed that cytosporones, and possibly the related dothiorelones (Fig 2), are produced by members of Phomopsis, Cytospora, and Cytospora-like, although the distribution of these metabolites among different species in each genus is not known. No strain of chemotypes 2e5 was found to produce cytosporones or dothiorelones (Table 2).…”
Section: Discussionsupporting
confidence: 72%
“…are among the most commonly investigated endophytes (e.g. Huang et al 2008Huang et al , 2009Rukachaisirikul et al 2008;Yu et al 2008). We conducted a chemical investigation of a collection of Phomopsis spp.…”
Section: Discussionmentioning
confidence: 99%
“…190 Pichia membranificiens [sponge, Halichondria okadai, (Izu Peninsula, Japan)] was the source of the indole derivatives 205 and 206, modest DPPH radical scavengers. 190 Pichia membranificiens [sponge, Halichondria okadai, (Izu Peninsula, Japan)] was the source of the indole derivatives 205 and 206, modest DPPH radical scavengers.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…In our present study, Alternaria was also found to be frequent genera (13.1%) and show no infectious symptom to its host. Phomopsis is an important mangrove endophyte, and many significant new bioactive metabolites were isolated from this fungus [7,9,19,20].…”
Section: Discussionmentioning
confidence: 99%